In Vitro Study of Cytotoxic Mechanisms of Alkylphospholipids and Alkyltriazoles in Acute Lymphoblastic Leukemia Models - Larissa de Oliveira Passos Jesus; Aline Aparecida de Souza; Heron Fernandes Vieira Torquato; Vanessa Silva Gontijo; Rossimirian Pereira de Freitas; Tarsis Ferreira Gesteira; Vivien Jane Coulson-Thomas; Ricardo José Soares Torquato; Aparecida Sadae Tanaka; Edgar Julian Paredes-Gamero; Wagner Alves de Souza Judice (Molecules, 2022)
This study investigates the efficacy of miltefosine, alkylphospholipid, and alkyltriazolederivative compounds against leukemia lineages. The cytotoxic effects and cellular and molecular mechanisms of the compounds were investigated. The inhibitory potential and mechanism of inhibition of cathepsins B and L, molecular docking simulation, molecular dynamics and binding free energy evaluation were performed to determine the interaction of cathepsins and compounds. Among the 21 compounds tested, C9 and C21 mainly showed cytotoxic effects in Jurkat and CCRF-CEM cells, two human acute lymphoblastic leukemia (ALL) lineages. Activation of induced cell death by C9 and C21 with apoptotic and necrosis-like characteristics was observed, including an increase in annexin-V+propidium iodide−, annexin-V+propidium iodide+, cleaved caspase 3 and PARP, cytochrome c release, and nuclear alterations. Bax inhibitor, Z-VAD-FMK, pepstatin, and necrostatin partially reduced cell death, suggesting that involvement of the caspase-dependent and -independent mechanisms is related to cell type. Compounds C9 and C21 inhibited cathepsin L by a noncompetitive mechanism, and cathepsin B by a competitive and noncompetitive mechanism, respectively. Complexes cathepsin-C9 and cathepsin-C21 exhibited significant hydrophobic interactions, water bridges, and hydrogen bonds. In conclusion, alkyltriazoles present cytotoxic activity against acute lymphoblastic lineages and represent a promising scaffold for the development of molecules for this application.